Appraisal of Counsellor Learner Support Services in Open Distance Learning System - AINA, Josephine Shola (Ilorin Journal of Education, 2024)
Learning at a distance is similar to classroom learning in many ways, but there are some notable differences. Counsellors of distant learners must achieve the same general aims as those working in traditional settings, because the counsellor is separated from the learners, some of the obstacles take on new forms. For example, in the absence of counsellors, the learner is frequently insecure and concerned about his or her progress in the absence of close feedback and, possibly, fellow learners. The learner becomes more insecure if the course's direction is not effectively structured and it is unclear where he or she stands in terms of completion of his or her programme. The concept of "drop-out" is significantly more widespread in distant education than in traditional education, implying that it is simpler for a learner to withdraw from the somewhat impersonal interaction of a distance course than from a traditional curriculum. In response to such concerns, Open Distance Learning (ODL) counsellors must take a variety of steps to ensure that the course is well-structured, with clear objectives and an efficient use of learners' time. This article investigated the role of counsellors in the delivery of learner support services in the ODL system. This paper also discussed responsibilities of the counsellors in an Open University system in follow-up, monitoring of learners' progress, and feedback mechanisms.